Forest Fragmentation and Warmer Climate Increase Tick-Borne Disease Infection - Iijima, Hayato; Watari, Yuya; Doi, Kandai; Yasuo, Kazuhiro; Okabe, Kimiko (EcoHealth, 2025)
Anthropogenic disturbances degrade ecosystems, elevating the risk of emerging infectious diseases from wildlife. However, the key environmental factors for preventing tick-borne disease infection in relation to host species, landscape components, and climate conditions remain unknown. This study focuses on identifying crucial environmental factors contributing to the outbreak of severe fever with thrombocytopenia syndrome (SFTS), a tick-borne disease, in Miyazaki Prefecture, southern Japan. We collected data on SFTS case numbers, annual temperature and precipitation, species richness of large- and middle-sized mammals, forest perimeter length (indicating the amount of forest boundaries), percentage of agricultural land, human population, and sightseeing place numbers for each 25 km grid cell encompassing Miyazaki Prefecture. Through the construction of a model incorporating these factors, we found that longer forest perimeter and higher temperature led to a higher number of SFTS cases. Precipitation, mammal species richness, percentage of agricultural land, human population, and sightseeing point numbers had no effect on SFTS case numbers. In conclusion, climate condition and forest fragmentation, which increase the opportunity for human infection, played a pivotal role in SFTS outbreak.